Coronary artery disease in East and South Asians: differences observed on cardiac CT. Issue 4 (13th May 2021) - Chua, Alexander; Adams, Daniel; Dey, Damini; Blankstein, Ron; Fairbairn, Timothy; Leipsic, Jonathon; Ihdayhid, Abdul Rahman; Ko, Brian
Abstract : Epidemiological studies have observed East Asians (EAs) are significantly less likely to develop or die from coronary artery disease (CAD) compared with Caucasians. Conversely South Asians (SAs) develop CAD at higher rate and earlier age. Recently, a range of features derived from cardiac CT have been identified which may further characterise ethnic differences in CAD. Emerging data suggest EAs exhibit less coronary calcification and high-risk, non-calcified plaque compared with Caucasians on CT, with no difference in luminal stenosis. In contrast, SAs exhibit similar to higher coronary calcification and luminal stenosis, smaller luminal dimensions and more high-risk, non-calcified plaque than Caucasians. Beyond demonstrating ethnic differences in CAD, cardiac CT may enhance and individualise cardiovascular risk stratification in EAs and SAs. While data thus far in EAs have demonstrated calcium score and CT-derived luminal stenosis may incrementally predict cardiovascular risk beyond traditional risk scores, there remains a paucity of data assessing its use in SAs. Future studies may clarify the prognostic value of cardiac CT in SAs and investigate how this modality may guide preventative therapy and coronary intervention of CAD in EAs and SAs.